TEXTBOOK EVALUATION: AN ANALYSIS OF LISTENING AND READING SKILL IN PROJECT LEVEL 1 (4 TH 77 EDITION) AND ACHIEVERS A1+ - Min, Lee Sun; Floris, Flora Debora (Universitas PGRI Adi Buana Surabaya, 2017)
The present study evaluates the presentation of listening andreading skills in Project level 1 (4th edition) and Achievers A1+ textbooks.The textbooks were evaluated by using the theoretical framework asproposed by Cunningsworth (1995). This research used qualitative contentanalysis as its research method. The results of this study show that bothtextbooks met the evaluation criteria proposed by Cunningsworth (1995)regarding the presentation of the listening skill. As for the presentation ofthe reading skill, Project level 1 (4th edition) textbook was considered asadequately met the requirement; while Achievers A1+ might be morerelevant to the evaluation criteria.